RESEARCH IN DESIGNING CONTROL SMART HOME SYSTEM - Võ Minh Phụng; Dương Thị Thanh Hiên; Võ Tiến Phúc (Tạp chí Khoa học Đại học Đà Lạt)
Smart home systems capable of connecting electrical equipment, interacting with the user to control devices of convenience, or operating according to a pre-installed schedule were investigated. In this study, the authors built a model smart home system capable of receiving signals from environmental sensors by connecting the electrical equipment in the house to a network through wireless technologies, such as Bluetooth and Global System Mobile (GSM). The devices are controlled via software on a smartphone. By understanding the existing smart home system and comparing the implemented solutions, the new technology is now more suitable. The authors have created a product model that meets the stated objectives: it is feasible for deployment in the smart house system, serves for routine operation by a family to add comfort, is modern, and is easy to install with reasonable costs.